62.0k views
3 votes
Y is six more than x divided by three

turn it into an expression (y=mx+b format)

User Ffff
by
6.2k points

1 Answer

4 votes

We always start from right side in order of operation in any equation

we can set up equation as

step-1:

x divided by three

we can write as


=(x)/(3)

step-2:

six more than x divided by three

so, we get


=(x)/(3)+6

step-3:

y is six more than x divided by three

so, we get


y=(x)/(3)+6

and this is in y=mx+b form

so, we have


y=(x)/(3)+6...............Answer


User Zantier
by
6.5k points